Pemetaan Kerawanan Banjir Berbasis Multi-Criteria Analysis (MCA) Berbasis Google Earth Engine dan SIG di Kota Medan - Ari Paskalis Stefanus Hutagalung; Yahya Darmawan; Widodo Widodo (Universitas Budi Luhur, 2025)
Flooding is a frequent hydrometeorological disaster in urban areas that significantly impacts the environment, infrastructure, and socio-economic activities. As a major metropolitan city in Indonesia, Medan faces a high level of flood vulnerability due to its predominantly low-lying topography, high building density, and proximity to river networks. This study aims to map flood vulnerability levels in Medan City for the year 2025 using a Multi-Criteria Analysis (MCA) approach based on Google Earth Engine (GEE), integrating the Topographic Wetness Index (TWI) as a novel element. The parameters utilized include distance from rivers, elevation, Topographic Position Index (TPI), Normalized Difference Vegetation Index (NDVI), and TWI. Each parameter was classified into five classes and weighted based on its contribution to flood risk, then aggregated to produce a final flood vulnerability index. The results indicate that Medan is dominated by a moderate level of flood vulnerability, while high-vulnerability zones are primarily concentrated in low-lying areas near rivers with high TWI values. The integration of TWI proved effective in increasing the model's sensitivity in identifying potential surface water accumulation. Consequently, the resulting flood vulnerability map provides a more comprehensive representation of the region's physical and hydrological conditions.